Implementasi Sistem Monitoring Laporan Kerja Praktek Lapangan Berbasis Web Pada SMK Citra Madani Kabupaten Tangerang - Aris; Hose Munthe, Nuel; Ikhwanul Hartanto, Farix; Ahmad Syampurna, Dimas (Technomedia Journal, 2022)
Based on the ongoing analysis, the results show that the current system still has a number of deficiencies and still requires a lot of further developments. The current system is still being worked on manually, so that the reports generated are not accurate, the existing data cannot be recorded properly, there is no adequate security system and the running system has not been able to produce a monitoring information system quickly and accurately. In conducting direct observations at SMK Citra Madani, the report describes efforts to control student activities / activities in the implementation of field work practices, efforts to control this occur because many students cheat by not attending / coming to the company and assignment reports that are still not effective. In this study, using PHP programming and MySql data base to create online applications, as well as designing with UML which is implemented can help teachers and field supervisors monitor the activities of student fieldwork reports. Keywords: Monitoring System, Job Training